Technique notes on the management of superior sagittal or transverse sinus during the falcotentorial meningioma surgery: a case report - Liu, Jun; Fan, Di; Chen, Ligang; Zou, Zheng; Li, Xinning; Zhou, Minghao; Wen, Zhongcheng; Gong, Shun; Liang, Guobiao (Frontiers in Neurology, 2024)
Background Falcotentorial meningiomas (FM) are surgical challenges for protecting sinus, and the technique notes on the management of superior sagittal or transverse sinus are required for good results. Methods We improved the technique notes on the management of superior sagittal or transverse sinus in three FM patients with signs of increased intracranial pressure or chronic headache. Results All patients underwent surgeries in the prone position, and occipital/sup-occipital/sub-occipital craniotomy was performed. In one patient, the skull was removed traditionally with exposure of the confluence of sinuses, superior sagittal, and transverse sinus, while the longitudinal skull bridge was left to suspend the dura for protecting the superior sagittal sinus in one patient, and the transverse skull bridge was left to suspend the dura for protecting the transverse sinus in one patient. The dura was opened infratentorially or supratentorially to spare the sinus and then the “skull bridge” was suspended. The tumor was then removed completely without brain swelling or significant venous bleeding. Complete tumor resection was confirmed by early postoperative imaging, and all patients recovered well without postoperative morbidity. Conclusion The authors recommend the “skull bridge” to suspend the dura for optimal control of the venous sinuses during FM surgery (less venous bleeding).